Sierra Leone : Second and Third Reviews Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Waivers of Nonobservance of Performance Criteria, Request for Modification of Performance Criteria, and Financing Assurances Review: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Sierra Leone. (IMF Staff Country Reports; Country Report ;, 2011)
Sierra Leone's economic activity is expanding, and the medium-term outlook is favorable. Real GDP growth picked up to about 5 percent in 2010-11, while the commencement of an iron ore megaproject in 2012 is expected to boost GDP and exports substantially. Fiscal tightening, through strengthening of revenue collection and containing domestically financed capital spending, along with reduced central bank direct credit to government, ensured that program ceilings for net credit to government and net domestic assets were met by substantial margins in June 2011.